2011
DOI: 10.1016/j.ejpoleco.2010.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Political competition, electoral participation and public finance in 20th century Latin America

Abstract: Rational choice models predict that political competition and political participation have opposite e¤ects on the size of government. We investigate these theories using data from a panel of 18 Latin American countries during the 20th century. Our research builds evidence for the prediction that reforms enhancing political competition tend to limit the size of government, while reforms increasing political participation tend to increase the size of government. Furthermore, we …nd that reforms which remove lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 55 publications
2
41
1
1
Order By: Relevance
“…Some of the existing studies consider the relationship between democracy and the total amount of the public sector. Aidt and Eterovic (2011) suggest that political competition appears to be negatively correlated with the government size, while the opposite is true for political participation. Moreover, Plümper and Martin (2003), Hausken et al (2004) and Aidt et al (2010) find a U-shaped relationship between democracy and public spending.…”
Section: -Review Of Theoretical and Empirical Literaturementioning
confidence: 86%
“…Some of the existing studies consider the relationship between democracy and the total amount of the public sector. Aidt and Eterovic (2011) suggest that political competition appears to be negatively correlated with the government size, while the opposite is true for political participation. Moreover, Plümper and Martin (2003), Hausken et al (2004) and Aidt et al (2010) find a U-shaped relationship between democracy and public spending.…”
Section: -Review Of Theoretical and Empirical Literaturementioning
confidence: 86%
“…4 Using data from the Encyclopaedia Britannica and other sources, we found that 28 of the 43 large changes in the democracy measure in our sample involved democratic concessions by the incument government. 5 The work by Berger and Spoerer (2001), however, indicates that there was a strong link between poor economic conditions and the European revolutions of 1848. 6 Franck (2012) establishes a causal link between short-term variations in local tax income (instrumented by rainfall levels) in 19th century France and electoral support for democratic institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically, competitiveness has been tested in only developed 14 To our knowledge, the rst to introduce the idea is Frey and Schneider (1978), who nd that in the US current spending decreases with the incumbent's popularity. countries and only sub-national level (Schultz, 1995;Price, 1998;Alt and Rose, 2009;Aidt and Eterovic, 2011;Pettersson-Lidbom, 2001;Schneider, 2010 rejects government requests for funding, or rejects budgets altogether, it is often a consequence of a strong and well-organized opposition able to break the voting discipline of the governing party or coalition. Note: The shaded areas represent the empirical distribution of regimes along the two dimensions; darker areas signify more observations.…”
Section: Electoral Competitivenessmentioning
confidence: 99%
“…The variable is measured as a share of the gross national income and taken from World Bank (2010) and OECD (2015) respectively. Finally, it might be the case that more experienced incumbents are more skillful in manipulating spending opportunistically (Aidt and Eterovic, 2011). We control for this possible Tenure eect by including a count variable of the number of years an incumbent has been in oce, using the Archigos dataset (Goemans et al, 2009 Based on this nding, it could be argued that we should control for universal surage.…”
mentioning
confidence: 99%